2010
DOI: 10.1667/rr2160.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Radiation on the Immune System of Mice after Total-Body Irradiation

Abstract: The effects of acute exposure to low- and high-dose radiation on the quantitative and functional parameters of the immune system were analyzed. C57BL/6 mice were irradiated with different doses of γ radiation (0.01, 0.05, 0.1, 0.5 and 2 Gy) and splenocytes were isolated at various times. Alterations in the distribution and surviving fraction of splenocyte subsets such as CD4(+) and CD8(+) T lymphocytes, regulatory T cells (Treg), natural killer (NK) cells, dendritic cells (DCs) and B lymphocytes were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 40 publications
9
106
0
1
Order By: Relevance
“…In some cases, injection of a high dose could be problematic. It depends on the ability to produce concentrated tracer, raises the potential for a mass effect (e.g., in receptor studies) (17), and may bring confounds from the absorbed dose received by the mouse (18,19). The applications for which clustered-pinhole PET is superior to coincidence PET are limited but include commonly performed 18 F-FDG imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, injection of a high dose could be problematic. It depends on the ability to produce concentrated tracer, raises the potential for a mass effect (e.g., in receptor studies) (17), and may bring confounds from the absorbed dose received by the mouse (18,19). The applications for which clustered-pinhole PET is superior to coincidence PET are limited but include commonly performed 18 F-FDG imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the development of a neuropathological immune response and the contribution of host CD4 ϩ T and CD8 ϩ T cells to ECM were preserved, it is difficult to appreciate the whole systemic effects (endothelium, microglia, intestinal flora) in addition to the immunomodulatory effect of low-dose total-body irradiation (35)(36)(37)(38)(39) in our model. Similarly, we are not able to appreciate how the infection and neuropathogenesis could modulate the irradiation effect, which develops over time (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of Treg cells in irradiated mice was also reported in MRL-lpr/lpr mice, used as an animal model for SLE , and EAE mice, used as an animal model for MS . On the other hand, Bogdándi et al (2010) reported no significant change in the percentage of CD4 + CD25 + Foxp3 + Treg cells in normal C57BL/6 mice after one single 0.5Gy γ-irradiation. A difference may exist between normal mice and disease mouse models.…”
Section: Foxp3mentioning
confidence: 92%
“…The effects of low-dose irradiation on the immune system were examined by determining time-dependent numerical changes in various lymphocyte subsets (Bogdándi et al 2010 …”
Section: T-cell Subpopulationsmentioning
confidence: 99%